Research on Moral Judgment Competency of College Students in Mainland China with DIT-2 - Zhang, Qian; Thoma, Stephen J. (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2017)
The purpose of this paper was to (1) examine moral judgment competency of a sample of 811 Chinese college students from a Southern university in mainland China with DIT-2; and (2) test whether gender, education, major, academic performance, and one-child policy have significant effect on the participants’ moral judgment competency. Results show that the participants score high in both Personal Interest schema and Postconventional schema, while low in Maintaining Norms schema. Gender and major have significant effect on participants’ moral judgment competency in China, while education level, academic performance and one-child family have no significant effect on their moral judgment competency. Reasons are discussed in the paper.
Keywords: DIT-2; moral judgment competenc; college student; Chinese participants